Persepsi Guru dan Siswa Terhadap Penerapan Kurikulum Merdeka Mata Pelajaran Biologi di SMA Negeri 1 Luwuk - Koida, Dewi Kartika; Kenta, Abd. Muin; Haluti, Armin; Haruna, Moh. Fahri (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2024)
Abstract: Their curriculum is a new policy that applies to all educational units in Indonesia. Teachers and students as components who feel changes from the curriculum in learning certainly raise perceptions. This study aims to determine (i) teachers' perceptions of the implementation of an independent curriculum in biology subject at SMA Negeri 1 Luwuk, (ii) students' perceptions of implementing an independent curriculum in biology subject at SMA Negeri 1 Luwuk. This research uses a descriptive qualitative approach. The population of this study were 3 biology teachers and 352 class X students of SMA Negeri 1 Luwuk for the 2022/2023 academic year with a sample size of 3 biology teachers and 78 class X students. The student sampling technique used a random sampling technique. Data collection techniques used by means of interviews and distribution of instruments. Data were analyzed using a qualitative descriptive method. The results of this study indicate that (i) there are still many obstacles faced by teachers in understanding the independent curriculum, so it is still very necessary to provide independent curriculum training at schools, provinces and the center. While in terms of the facilities and infrastructure available at SMA Negeri 1 Luwuk it can be said to be good as a support for biology learning towards the implementation of the Merdeka curriculum, (ii) Students' perceptions of the implementation of the independent curriculum for biology subjects are good.